Maintaining the CRRT Circuit: Non anticoagulant alternatives. - Davies, H.; Leslie, Gavin (Elsevier, 2006)
Prevention of clotting is an important factor in continuous renal replacement therapy (CRRT) to ensure that solute clearance, electrolytes and acid base and fluid balance are controlled. This article will focus attention on the components and design of the CRRT circuit, identifying strategies in the literature which n~ay promote circuit life. It is important that the CRRT circuit incorporates biocompatible materials and is designed in a way which limits turbulent blood flow. Premature clotting is also more likely to occur when blood flow through the circuit is interrupted or sluggish as a result of poor vascular access, or when there is increased resistance or obstruction in the circuit. The pre-dilution method of fluid replacement reduces blood viscosity inside the haemofilter and assists in delaying the onset of blood clots by limiting the potential for haemoconcentration. The monitoring and adjustment of the blood level inside the venous bubble or air trap ca:: lessen the effect of blood-air contact and protect the site from excessive clotting. A number of other factors are also considered important as predictors of circuit life in the operation and management of the circuit. They include the choice of access site and design configuration of the catheter device, and the level of competency of nursing staff preparing and monitoring circuit function. Whilst the value of intem:ittent saline flushing has not been proven to be of benefit in promoting circuit life, it remains to be detem:ined whether the choice in the CRRT mode affects circuit life differently. In conclusion, specific measures in the application of CRRT besides anticoagulation therapy ca:: influence the development of blood clots and the duration of circuit life. This requires the development of evidence-based practice guidelines which include strategies that are known to promote circuit life.